Study on Isolated Staphylococcus aureus from Bovine Milk with Mastitis Containing Methicillin and Panton-Valentine Leukocidin Gene - Maryam Gharghi; Nima Bahador; Abbas Rowshan-Ghasrodashti (Pizhūhish va Nuāvarī dar ̒Ulūm va Sanāyi̒-i Ghaz̠āyī, 2022)
Nowadays, bovine mastitis has been recorded as an inflammation of the mammary gland and Staphylococcus aureus is the main pathogens responsible for contagious mastitis in ruminants. Presented study is looking for to assess the existence of methicillin-resistant and PVL positive Staphylococcus aureus from bovine milk and if there is any relation among the detected genes and antibiotic resistance or not? For this purpose, 100 milk samples were collected from cows affected with mastitis from four dairy farms in Fars province. The samples were transferred to MSA medium and incubated at 37 °C for 24 h. The pure colonies were identified by biochemical as well as molecular techniques using mecA, mecC and PVL gene. Then, the antibiotic pattern of the isolates was analyzed based on CLSI 2019 and Whonet program. Finally, the results were analyzed using statistical analysis. Totally, 6 S. aureus strains were detected which was confirmed by biochemical as well as molecular techniques. The isolates showed different antibiotic susceptibility patterns, most of the isolates were multidrug resistant, while, the strain No. 5 was the most sensitive one. Our results indicated presence of mecA gene in strains 1, 2 and 3, mecC in isolates 4, 5 and 6, and the PVL gene only in strain 4. Hence, it could be concluded that although different phages transporting PVL genes to the S. aureus isolate, in this special research we didn’t find any relationship between presence of mecA, mecC, and PVL genes with antibiotics resistant pattern.